Theories Supported Transfer of Learning to the Workplace - Zainon, Mat Sharif; Mohmad Yazam, Sharif (2014)
The aim of the paper is to discuss some insights into the role of science fiction-based films in television as well as in movie in inspiring the careers of some professionals. For decades, scholars thought that science fiction films are pure entertainment and are meant for children. Many do not know that these science fiction films have inspired children to pursue education and careers which influence the world. These youngsters in the 1960s later joined organizations such as the USA’s National Aeronautics Space Agency (NASA), which is in charge of America’s space travel programs, as scientists and space pilots. Others became scientists and engineers in telecommunications sector who invented many computer gadgets and telecommunication equipments which initially just appear as gadgets in science fiction films. They have converted science fiction into science fact. This paper used ‘The Star Trek’ film and TV episodes, one of the pioneering science fiction films in the 1960s, initially made as a film on television and later made into wide screen movies. The Star Trek phenomenon had been claimed to inspire some prominent professionals to venture into their chosen careers. A content analysis of website sources on the Star Trek phenomenon was made to uncover a few of these claims. This paper did not prove anything but only provided some indicators that fictional characters can inspire people in their career selection.